Larvicidal, leishmanicidal, insecticidal and anthelmintic effects of Sterculia diversifolia stem bark and leaf (Bangladesh Journal of Pharmacology, 2020)
The present study was conducted to evaluate the stem bark and leaf of Sterculia diversifolia for larvicidal, leishmanicidal, insecticidal and anthelmintic activities. In the larvicidal activity, dichloromethane and ethyl acetate fractions of both stem bark and leaf showed significant results, while the ethyl acetate fraction showed mild activity (IC50: 70.09 ± 0.09 μg/mL; 71.25 ± 0.01 μg/mL). In the insecticidal activity of the stem bark, n-hexane fraction showed mild activity (20-40% mortality) against all three subjects, while the insecticidal activity of leaf, methanolic extract and n-hexane fractions showed moderate activity (60% mortality) against Rhyzopertha dominica and Callosobruchus analis. In the anthelmintic activity of stem bark and leaf, ethyl acetate fraction exhibited activity in a dose-dependent manner giving time of paralysis and death shorter followed by dichloromethane fraction with 200 mg/mL concentration. Hence, it is clear that S. diversifolia stem bark and leaf possess larvicidal, leishmanicidal, insecticidal and anthelmintic agents.Video Clip of Methodology:Anthelmintic Activity: 5 min 29 sec:  Click to watch